Institucional Communication on Websites - Gómez López, Jacinto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Nowadays, institutions are not isolated entities, but are systems in constant interrelation with society. Like people, organizations have a way of working that they transmit through all their communicative acts, as well as a public image that in the information society is conveyed through their websites. The analysis of these from the technical and structural point of view and the adoption of new communication tools, social networks, describes the approach that institutions have to the uses of digital communication in today’s society.